Role of c-MET Inhibitors in Overcoming Drug Resistance in Spheroid Models of Primary Human Pancreatic Cancer and Stellate Cells - Firuzi, Omidreza (Cancers (Basel), 2019)
Pancreatic stellate cells (PSCs) are a key component of tumor microenvironment in pancreatic ductal adenocarcinoma (PDAC) and contribute to drug resistance. c-MET receptor tyrosine kinase activation plays an important role in tumorigenesis in different cancers including PDAC. In this study, effects of PSC conditioned medium (PCM) on c-MET phosphorylation (by immunocytochemistry enzyme-linked immunosorbent assay (ELISA)) and drug response (by sulforhodamine B assay) were investigated in five primary PDAC cells. In novel 3D-spheroid co-cultures of cyan fluorescence protein (CFP)-firefly luciferase (Fluc)-expressing primary human PDAC cells and green fluorescence protein (GFP)-expressing immortalized PSCs, PDAC cell growth and chemosensitivity were examined by luciferase assay, while spheroids’ architecture was evaluated by confocal microscopy. The highest phospho-c-MET expression was detected in PDAC5 and its subclone sorted for “stage specific embryonic antigen-4” (PDAC5 (SSEA4)). PCM of cells pre-incubated with PDAC conditioned medium, containing increased hepatocyte growth factor (HGF) levels, made PDAC cells significantly more resistant to gemcitabine, but not to c-MET inhibitors. Hetero-spheroids containing both PSCs and PDAC5 (SSEA4) cells were more resistant to gemcitabine compared to PDAC5 (SSEA4) homo-spheroids. However, c-MET inhibitors (tivantinib, PHA-665752 and crizotinib) were equally effective in both spheroid models. Experiments with primary human PSCs confirmed the main findings. In conclusion, we developed spheroid models to evaluate PSC–PDAC reciprocal interaction, unraveling c-MET inhibition as an important therapeutic option against drug resistant PDAC.